Լիդեր-քաղաքական գործչի հոգեբանական բնութագրերը - Շափաղաթյան, Հասմիկ (Զանգակ հրատ.)
Анализ проблемы показывает, что, несмотря на разнообразие теоретических и практических концепций в области изучения личности, каждая из них имеет базовые принципы, сочетание которых дает возможность глубокого и всестороннего анализа становления и развития личности политического лидера. В статье подчеркиваются политические и психологических факторы, способствующие формированию личности в период детства и юности, которые приводят к формированию уникальных личностных качеств политического лидера (наргизация, идентификация, комплексы неполноценности и доминирования). Эти качества в дальнейшем определяют как направление развития личности в качестве лидера, так и влияют на осуществление эффективной национальной политики. The analyses of the discussed problem shows that despite a diversity of studies on theoretical and practical concepts in the sphere of personality developments, each of them has some basic principals a combination of which provides an opportunity to make an in-depth and comprehensive analysis of the formation and the development of a personality of a political leader. The article emphasizes the political and psychological factors contributing to the formation of personality during childhood and adolescence, which lead to the formation of a unique personal qualities of a political leader (nargization, identification, as well as factors of formation and expression of inferiority and domination), which further define the direction of the person as a leader, as well as the implementation of effective and in the true sense of the word the course of their national policy.
Keywords: Հոգեբանություն